Arabs and Iranians in the Islamic Conquest Narrative - Savran, Scott, author.
1 online resource (304 pages)
Keywords: Arabs and Iranians in the Islamic Conquest Narrative analyzes how early Muslim historians merged the pre-Islamic histories of the Arab and Iranian peoples into a didactic narrative culminating with the Arab conquest of Iran. This book provides an in-depth examination of Islamic historical accounts of the encounters between representatives of these two peoples that took place in the centuries prior to the coming of Islam. By doing this, it uncovers anachronistic projections of dynamic identity and political discourses within the contemporaneous Islamic world. It shows how the formulaic placement of such embellishment within the context of the narrative served to justify the Arabs’ rise to power, whilst also explaining the fall of the Iranian Sasanian empire. The objective of this book is not simply to mine Islamic historical chronicles for the factual data they contain about the pre-Islamic period, but rather to understand how the authors of these works thought about this era. By investigating the intersection between early Islamic memory, identity construction, and power discourses, this book will benefit researchers and students of Islamic history and literature and Middle Eastern Studies.